The Role of Islamic Religious Education on Behavior and Competition in the World of Work - nela melani; pipit nurhayati; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - Islamic education today is faced with the challenges of modern human life that are filled with various problems that are quite complex; among others is